2013
DOI: 10.1111/bph.12309
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of skin differentiation genes by phytocannabinoids

Abstract: BACKGROUND AND PURPOSEEndocannabinoid signalling has been shown to have a role in the control of epidermal physiology, whereby anandamide is able to regulate the expression of skin differentiation genes through DNA methylation. Here, we investigated the possible epigenetic regulation of these genes by several phytocannabinoids, plant-derived cannabinoids that have the potential to be novel therapeutics for various human diseases. EXPERIMENTAL APPROACHThe effects of cannabidiol, cannabigerol and cannabidivarin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 81 publications
(141 reference statements)
1
72
0
2
Order By: Relevance
“…Of note, cannabinoids have been recently reported to regulate epigenetic modifications in both health and disease via chemical interactions with epigenetic enzymes, and through interactions with DNA repair mechanisms Pucci et al 2013;Lotsch et al 2013;Yang et al 2014). This appears particularly important, because targeting cannabinoid signaling might serve as a potentially innovative strategy to suppress the expression of proinflammatory genes, while activating that of anti-inflammatory genes, overall regulating the intricate immunologic responses within the brain.…”
Section: Cannabinoid-mediated Integration Of Brain Immunitymentioning
confidence: 99%
“…Of note, cannabinoids have been recently reported to regulate epigenetic modifications in both health and disease via chemical interactions with epigenetic enzymes, and through interactions with DNA repair mechanisms Pucci et al 2013;Lotsch et al 2013;Yang et al 2014). This appears particularly important, because targeting cannabinoid signaling might serve as a potentially innovative strategy to suppress the expression of proinflammatory genes, while activating that of anti-inflammatory genes, overall regulating the intricate immunologic responses within the brain.…”
Section: Cannabinoid-mediated Integration Of Brain Immunitymentioning
confidence: 99%
“…In this system, CBD behaves as a transcriptional repressor controlling cell proliferation and differentiation (698).…”
Section: Introduction: Cannabis and Cannabinoids Ancient Drugs Bementioning
confidence: 99%
“…CBG, like CBD, inhibits human keratinocyte proliferation and differentiation via non-CB1, non-CB2-dependent epigenetic mechanisms (698,916), and these effects may suggest its use against psoriasis and acne. CBG also shows antitumor activity in vitro (478).…”
mentioning
confidence: 99%
“…The same group has now reported that treatment of differentiated human keratinocytes cells with CBD significantly increased DNA methylation of keratin 10 gene. In addition, CBD increased global DNA methylation levels by selectively enhancing DNA methyltransferase DNMT1 expression, without affecting DNA methyltransferases DNMT 3a, 3b or 3L (Pucci et al, 2013). Vogel's group has recently shown that the CBD anti-inflammatory effects are mediated mainly by downregulating the expression of proinflammatory genes and upregulation of genes encoding negative regulators of NF-κB and AP-1 transcriptional activities .…”
Section: Cannabidiol (Cbd)mentioning
confidence: 97%